(untitled) (Italian Review of Legal History, 2015)
In 1806 Luosi submitted its draft penal code to Romagnosi, which wrote a new draft code, the Progetto sostituito, and wrote the Motivi. In this essay I’ll examine an instrument ingenious and terrible, the flogging machine, and the philosophy of punishment that prevailed in the first decade of the nineteenth century in Italy. In that period the achievements of the Enlightenment mingled with emerging repressive maneuvers.